1996
DOI: 10.1007/bf00436454
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes of Cryptococcus neoformans isolated from patients prior to and during the AIDS era in Thailand

Abstract: One hundred and eighty-seven strains of Cryptococcus neoformans isolated from patients in Thailand were characterized by biochemical varieties relating to serogroups. Canavanine-glycine-bromothymol blue (CGB) agar was used for differentiating the varieties of C. neoformans. Slide agglutination tests were performed with Crypto Check (Iatron, Inc., Tokyo) to determine their serotypes. Fifty-five percent (10 out of 18) of the pre-AIDS isolates were serotype B, 28% were serotype A, 5% were serotype D, and an unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 21 publications
5
21
0
Order By: Relevance
“…While VNI and VGI molecular types were equally predominant in the earlier cases of cryptococcosis (40.9 and 54.4%, respectively), VNI was the most predominant type isolated in recent cases of cryptococcosis (84.6%). This changing pattern of cryptococcal isolates has also been documented for serotypes of the C. neoformans from Thailand [24], another Southeast Asian country, prior to and during the AIDS era.…”
Section: Resultsmentioning
confidence: 89%
“…While VNI and VGI molecular types were equally predominant in the earlier cases of cryptococcosis (40.9 and 54.4%, respectively), VNI was the most predominant type isolated in recent cases of cryptococcosis (84.6%). This changing pattern of cryptococcal isolates has also been documented for serotypes of the C. neoformans from Thailand [24], another Southeast Asian country, prior to and during the AIDS era.…”
Section: Resultsmentioning
confidence: 89%
“…It was subsequently demonstrated that the most prevalent serotype in the United States was A (25) and that the dominant serotype in Thailand changed with the emergence of AIDS (378). The usefulness of serotyping C. neoformans has been confirmed by the large number of studies employing the method-more than 150 studies were identified in a MedLine search of the bibliography database in 1998, and that represented an underestimate.…”
Section: Biotyping Is Inadequate As a Dna Fingerprinting Methodsmentioning
confidence: 99%
“…Indeed, a change in the dominant serotype of C. neoformans accompanied the emergence of AIDS in Thailand (378). In addition, there is evidence of rapidly emerging pathogens such as C. glabrata (136) and C. dubliniensis (79,376) and changes in the proportions of dominant strains of C. albicans within a geographical locale over time (D. R. Soll, unpublished observations).…”
Section: Problems Of Collectionmentioning
confidence: 99%
“…Most clinical serotype C strains were isolated from immunocompetent patients in southern California [3]; in addition, there are reports of the isolation of serotype C from immunocompetent patients in Canada [3], the United Kingdom [3], Thailand [4], Mexico [5], Brazil [6], and Colombia [7]. On the basis of molecular fingerprinting, all serotype C strains have been associated with either of 2 genetically isolated molecular types, VGIII and VGIV [5].…”
mentioning
confidence: 96%